Interpersonal touch as a game interaction method - Marshall, Joe; Linehan, Conor; Tennent, Paul; Hazzard, Adrian (2016)
Interpersonal touch is a key element of social behaviour, yet is largely ignored in HCI. In this paper, we describe two games which explore two extremes of interpersonal touch, and discuss key research questions relating to them.